العوامل الأسریة المؤدیة إلى جنوح الأحداث - قلال مراد (كلية العلوم الاجتماعية, 2020)
Summary : The current study to know the familial factors that lead to juvenile delinquency sub questions emerged from them namely.the rise in the phenomenon of divorce that necessarily leads to juvenile delinquency? and does the order of factors leading to delinquency differ from one juvenile to another ? a sample of 03 male delinquents cases ranging in age from 15 to 18 years was chosen , and the study was based on the approach represented in : the clinical approach and case study, and also depending on the interview . the clinical observation and projective choice is repsented by the selection of the family fee by Louis corman ,and through this it was concluded that : 1- Family factors of all kinds push to juvenile delinquency. 2- The increase in the phenomenon of divorce leads to juvenile delinquency . 3- The order of factors leading to delinquency varies from event to event